(untitled) (SIRJANĀ – A Journal Of Arts and Art Education, 2022)
Mudrā as a divine sign language of the spiritual kind applied in religious rituals is essentially a means of communication and a bridge between physical existence and ultimate emancipation from non-existent existence envisaged in vajrayāna thought process. A pragmatic solution for final release from rebirths. It is a means of visualization for eventual realization. Interaction of sādhana, sādhya and sādhaka paves the way for nirvāņa through the formation of mudrās.